Impact of Ownership Structure and Corporate Governance on the Financial Performance of Jordanian Companies Listed in Amman Stock Exchange - Bataineh, Hanadi; Abed, Suzan; Suwaidan, Mishiel (Jordan Journal of Business Administration, 2019)
This study aims at examining the impact of ownership structure (family and non-family) and corporate governance on the financial performance of Jordanian companies listed in Amman Stock Exchange during the period (2010-2014). Corporate governance is measured by board size, board members’ ownership of the company’s shares, board independence, educational background of board members, duality of chairman and CEO roles and institutional ownership. On the other hand, the financial performance is measured by using Tobin’s Q. Four variables are employed in the study: (firm size, firm age, debt ratio and sector type) as control variables. The sample of this study consisted of 92 manufacturing and service companies listed in Amman Stock Exchange during the period (2010-2014). The sample is classified into 58 family - owned companies and 34 non-family-owned companies. The total number of observations was 460. Pooled data regression was conducted to achieve the objectives of the study. The results showed a statistically significant impact of the ownership structure (family and non-family) and corporate governance on the financial performance of all companies as measured by Tobin’s Q. The study also found out that the impact of corporate governance on the performance varies depending on the presence of family ownership. In light of these results, the study recommends corporate companies in general and family-owned companies in specific to comply with the corporate governance instructions as issued by the Jordanian Securities Commission. Family-owned companies should put a formal succession plan for senior management positions in order to ensure business continuity and thus increase chances of survival of family companies. The purpose of this plan is to ensure that the proposed senior managers have the required skills and leadership capabilities to run the organization in case of replacement